Now it Makes More Sense: How Narratives Can Help Atypical Actors Increase Market Appeal - Cutolo, Donato; Ferriani, Simone (Sage Journals, 2023)
Extensive research shows that atypical actors who defy established contextual standards and norms are subject to skepticism and face a higher risk of rejection. Indeed, atypical actors combine features, behaviors, or products in unconventional ways, thereby generating confusion and instilling doubts about their legitimacy. Nevertheless, atypicality is often viewed as a precursor to sociocultural innovation and a strategy to expand the capacity to deliver valued goods and services. Contextualizing the conditions under which atypicality is celebrated or punished has been a significant theoretical challenge for organizational scholars interested in reconciling this tension. Thus far, scholars have focused primarily on audience-related factors or actors’ characteristics (e.g., status and reputation). Here, we explore how atypical actors can leverage linguistic features of their narratives to counteract evaluative discounts by analyzing a unique collection of 78,758 narratives from crafters on Etsy, the largest digital marketplace for handmade items. Marrying processing fluency theory with linguistics literature and relying on a combination of topic modeling, automated textual analysis, and econometrics, we show that categorically atypical producers who make more use of abstraction, cohesive cues, and conventional topics in their narratives are more likely to overcome the evaluative discounts they would ordinarily experience.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 8 - Trabajo decente y crecimiento económico; ODS 9 - Industria, innovación e infraestructura; ODS 10 - Reducción de las desigualdades